A reforma trabalhista e a questão racial - Nascimento, Saulo Oliveira do (Universidade do Vale do Rio dos Sinos, 2023)
In 2017, Federal Law No. 13.467, known as the Labor Reform, came into effect, introducing significant changes in the realm of labor procedural law and workers' rights. The aim of this dissertation is to analyze the expectations and potential effects stemming from the legal changes introduced by the Reform Law on the Brazilian workforce, with a focus on the Black population, considering the enforcement of individual and collective rights. The methodology relied on bibliographic review, documentary research on national labor laws, exploration of sources and statistical indicators related to socioeconomic issues, and the production of primary data through semi-structured interviews with representatives from three companies and two unions. The research demonstrated immediate effects, such as a reduction in labor lawsuits, a decrease in unionization, and a significant decline in collective bargaining. However, the promised increase in job creation due to the Reform did not materialize. Yet, the research methodologically proved impossible to isolate economic variables to reach a conclusive statement regarding job creation and the Reform. Faced with these limitations, qualitative research shed light on subjective aspects, revealing that, on one hand, there was greater negotiation freedom and flexibility in hiring for the employer class, while on the other hand, there was an economic and representative weakening of the unions. The racial aspect was not quantifiable through secondary data, and the researched employers and unions lacked specific data. It was only possible to infer that the Black working population is likely more impacted compared to the White population, given their majority presence in the most vulnerable occupations. The research concludes that the effects, overall, unequally affected employees, professional unions, and companies, providing greater protections and possibilities for employers while offering less coverage of rights for the working class. Methodologically, the obstacles and limitations identified in this research provide clues for the development of a methodology capable of effectively analyzing labor reform in all its dimensions, enabling the isolation of its effects concerning other influencing factors and incorporating elements that can be studied through a racial lens.
Keywords: Reforma trabalhista; Mercado de trabalho; População trabalhadora negra; Proteção social; Labor reform; Labour market; Black working population; Social protection; ACCNPQ::Ciências Humanas::Sociologia